2017
DOI: 10.3847/1538-4357/aa8c0a
|View full text |Cite
|
Sign up to set email alerts
|

The JCMT Transient Survey: Detection of Submillimeter Variability in a Class I Protostar EC 53 in Serpens Main

Abstract: During the protostellar phase of stellar evolution, accretion onto the star is expected to be variable, but this suspected variability has been difficult to detect because protostars are deeply embedded. In this paper, we describe a sub-mm luminosity burst of the Class I protostar EC 53 in Serpens Main, the first variable found during our dedicated JCMT/SCUBA-2 monitoring program of eight nearby star-forming regions. EC 53 remained quiescent for the first 6 months of our survey, from February to August 2016. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 68 publications
6
64
0
Order By: Relevance
“…However, the freeze-out timescale could be longer than a few years when the maximum grain size is larger than 1 cm (see Section 4.1), since the total surface area of grains would then be reduced by a factor of ∼300, assuming that the total grain mass is conserved, and the minimum size of grain and the power-law index of grain size distribution are 0.1 µm and -3.5, respectively. This freeze-out timescale is longer than the periodicity of 1.5 years in the accretion onto EC 53 (Yoo et al 2017). The CH 3 OH emission could trace the water snow line constructed during the burst phase of the period, when the luminosity is four times brighter (Yoo et al 2017) and the water snow line would then be two times larger, or ∼0.06 ′′ (Min et al 2011;Jørgensen et al 2015;Visser et al 2015).…”
Section: Water and Co Snowlinesmentioning
confidence: 98%
“…However, the freeze-out timescale could be longer than a few years when the maximum grain size is larger than 1 cm (see Section 4.1), since the total surface area of grains would then be reduced by a factor of ∼300, assuming that the total grain mass is conserved, and the minimum size of grain and the power-law index of grain size distribution are 0.1 µm and -3.5, respectively. This freeze-out timescale is longer than the periodicity of 1.5 years in the accretion onto EC 53 (Yoo et al 2017). The CH 3 OH emission could trace the water snow line constructed during the burst phase of the period, when the luminosity is four times brighter (Yoo et al 2017) and the water snow line would then be two times larger, or ∼0.06 ′′ (Min et al 2011;Jørgensen et al 2015;Visser et al 2015).…”
Section: Water and Co Snowlinesmentioning
confidence: 98%
“…An embedded FU Ori-type object is difficult to observe directly as radiation is absorbed very close to the protostar and re-emitted at longer wavelengths (e.g. OO Serpentis, Kóspál et al (2007); NGC 6334l: MM1 Hunter et al (2017); HOPS 383, Safron et al (2015); EC 53, Yoo et al (2017)). Johnstone et al (2013) suggested that variations in the far IR through (sub-)mm emission from protostars might be observed as a proxy for episodic accretion, although they found that there may be a delay in the (sub-)mm response of weeks to months after the outburst has started.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as young protostars are deeply embedded in their parent envelopes the effect of an outburst may be difficult to observe, at least at optical wavelengths. Therefore, longer wavelength, observations may be more appropriate (e.g Kóspál et al 2007;Hunter et al 2017;Safron et al 2015;Yoo et al 2017).…”
Section: Introductionmentioning
confidence: 99%